Multilokusová charakteristika symbiontů entomopatogenních hlístovek rodu Steinernema - Faktorová, Lucie (Jihočeská univerzita, 2017)
During the evolution some groups of organisms have become coevolutionary associated with other groups, as is the case of host symbiont systems. To explore coevolutionary history of hosts and their associated symbionts, phylogenetic reconstruction of symbionts and phylogenetic reconstruction of hosts are usually compared. Coevolution is described by coevolutionary events (cospeciation, host switch, duplication, failure to diverge events and linage sorting events). The aim of this work was to test the suitability of MLST method for the complex of entomopathogenic nematodes from the genus Steinernema (with detailed analysis of Steinernema feltiae) and their symbiotic bacteria Xenorhabdus bovienii and subsequently use cophylogenetic comparative analysis to determine their level of cospeciation.
Multilocus characteristic symbionts of entomopathogenic nematodes from the genus Steinernema
Keywords: koevoluce; entomopatogenní hlístice; symbiotické bakterie; MLST; coevolution; entomopathogenic nematodes; symbiotic bacteria; MLST